Fostering Effective Early Learning (FEEL) through a professional development programme for early childhood educators to improve professional practice and child outcomes in the year before formal schooling: study protocol for a cluster randomised controlled trial. Issue 1 (December 2016) - Melhuish, Edward; Howard, Steven; Siraj, Iram; Neilsen-Hewett, Cathrine; Kingston, Denise; de Rosnay, Marc; Duursma, Elisabeth; Luu, Betty
Abstract Background A substantial research base documents the benefits of attendance at high-quality early childhood education and care (ECEC) for positive behavioural and learning outcomes. Research has also found that the quality of many young children's experiences and opportunities in ECEC depends on the skills, dispositions and understandings of the early childhood adult educators. Increasingly, research has shown that the quality of children's interactions with educators and their peers, more than any other programme feature, influence what children learn and how they feel about learning. Hence, we sought to investigate the extent to which evidence-based professional development (PD) – focussed on promotingsustained shared thinking through quality interactions – could improve the quality of ECEC and, as a consequence, child outcomes. Methods/design The Fostering Effective Early Learning (FEEL) study is a cluster randomised controlled trial for evaluating the benefits of a professional development (PD) programme for early childhood educators, compared with no extra PD. Ninety long-day care and preschool centres in New South Wales, Australia, will be selected to ensure representation across National Quality Standards (NQS) ratings, location, centre type and socioeconomic areas. Participating centres will be randomly allocated to one of two groups, stratified by centre type and NQS rating: (1) anintervention group (45 centres) receiving a PD intervention or (2) acontrol group (45 centres) that continues engaging in typical classroom practice. Randomisation to these groups will occur after the collection of baseline environmental quality ratings. Primary outcomes, at the child level, will be two measures of language development: verbal comprehension and expressive vocabulary. Secondary outcomes at the child level will be measures of early numeracy, social development and self-regulation. Secondary outcomes at the ECEC room level will be measures of environmental quality derived from full-day observations. In all cases, data collectors will be blinded to group allocation. Discussion This is the first randomised controlled trial of a new approach to PD, which is focussed on activities previously found to be influential in children's early language, numeracy, social and self-regulatory development. Results should inform practitioners, policy-makers and families of the value of specific professional development for early childhood educators. Trial registration Australian New Zealand Clinical Trials Registry (ACTRN) identifierACTRN12616000536460 . Registered on 27 April 2016. This trial was retrospectively registered, given the first participant (centre) had been enrolled at the time of registration.